Macromol. Mater. Eng. 8/2018. Issue 8 (10th August 2018) - Chen, Yunhua; Cheng, Wenhua; Teng, Lijing; Jin, Min; Lu, Bingheng; Ren, Li; Wang, Yingjun
Abstract : Front Cover : In article1700660, Li Ren, Yingjun Wang, and co‐workers, report a graphene oxide hybrid supramolecular hydrogel that can self‐heal with mechanical recovery, completed within seconds. The material has remarkable adhesive ability to various surfaces and biological tissues, and can be used as an adhesive coating on substrates for stimuli‐responsive drug release.